Land Reforms and the Conflicts over the Use of Land: Implication for the Vulnerability of Peasants in Rural China. (December 2017) - Cheng, Hongming
Statutes and policy documents, as well as open-ended interviews in Zhejiang, China, were used to identify key aspects of rural land law reforms in China to help develop the national economy. It has been observed that despite its positive effect on general rural economic development such development is compromised by extensive corruption that harms peasants' interests. Peasants face new forms of exploitation by local governments and businesses, as well as environmental damage caused by over-exploitation of land and resources that becomes a serious hurdle for sustainable development in rural areas.